Attentional processes, not implicit mentalizing, mediate performance in a perspective-taking task: Evidence from stimulation of the temporoparietal junction - Santiesteban, I; Kaur, S; Bird, G; Catmur, C (Elsevier, 2017)
Mentalizing is a fundamental process underpinning human social interaction. Claims of the existence of ‘implicit mentalizing’ represent a fundamental shift in our understanding of this important skill, suggesting that preverbal infants and even animals may be capable of mentalizing. One of the most influential tasks supporting such claims in adults is the dot perspective-taking task, but demonstrations of similar performance on this task for mentalistic and non-mentalistic stimuli have led to the suggestion that this task in fact measures domain-general processes, rather than implicit mentalizing. A mentalizing explanation was supported by fMRI data claiming to show greater activation of brain areas involved in mentalizing, including right temporoparietal junction (rTPJ), when participants made self-perspective judgements in a mentalistic, but not in a non-mentalistic condition, an interpretation subsequently challenged. Here we provide the first causal test of the mentalizing claim using disruptive transcranial magnetic stimulation of rTPJ during self-perspective judgements. We found no evidence for a distinction between mentalistic and non-mentalistic stimuli: stimulation of rTPJ impaired performance on all self-perspective trials, regardless of the mentalistic/non-mentalistic nature of the stimulus. Our data support a domain-general attentional interpretation of performance on the dot perspective-taking task, a role which is subserved by the rTPJ.